Analisis Pengaruh Brand Image, Consumer Behavior dan Price Terhadap Keputusan Pembelian Produk Scarlett (Studi Kasus Pada Pengguna Scarlett) - Alisman; Salsabilla, Raihan; Zakaria; Fahmi, Ijal; Sufriadi, Dedi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Scarlett is a brand originating from Indonesia, produced by PT. Opto Lumbung Sejahtera was founded at the end of 2017. Scarlett products are in first position, as the best-selling products in 2021. To increase sales and improve the company's brand image, Scarlett recently used a new Brand Ambassador to market its products. The aim of this research is to analyze the influence of Brand Image, Consumer Behavior and Price on purchasing decisions for Scarlett products. This research uses a questionnaire distributed via Google Form online and offline. The object of this research is the influence of Brand Image, Consumer Behavior and Price on purchasing decisions for Scarlett products made by consumers or users of Scarlett products. Based on the research results, it shows that brand image (X1), consumer behavior (X2) and price (X3) have a positive and significant effect on purchasing decisions for Scarlett products. This is evident from the significance value of the F test, namely 0.000 < 0.05. So from these results it can be concluded that the hypothesis which states that brand image, consumer behavior and price influence the decision to purchase Scarlett products is accepted.